Current and emerging triplet combination therapies for relapsed and refractory multiple myeloma. Issue 3 (3rd March 2016) - Pantani, L.; Brioli, A.; Tacchetti, P.; Zannetti, B.A.; Mancuso, K.; Rocchi, S.; Martello, M.; Rizzello, I.; Terragna, C.; Zamagni, E.; Cavo, M.
ABSTRACT: Despite significant improvement in outcomes have been observed for multiple myeloma (MM) patients over the past 10–15 years, mainly due to the introduction of novel agents targeting the tumor clone and the bone marrow microenvironment, treatment of refractory and/or relapsed (RR) disease remains a challenge, particularly for patients who have failed prior bortezomib- and lenalidomide-based therapies. More recently, new drugs with different mechanisms of action, including second generation proteasome inhibitors, third generation immunomodulatory drugs, histone deacetylase inhibitors and monoclonal antibodies, have been developed and are under investigation, further increasing treatment options for RRMM patients. Overall, novel agent-based triplet combinations demonstrated superior response rates and prolonged disease control when compared with two-drug regimens in several randomized clinical trials, without adding any relevant additional toxicity. Salvage triplet therapies are likely to play a key role in overcoming drug-resistance and hold promise to further improve long-term outcomes of RRMM patients.